Mode-locked thulium fiber laser with MoS2. (30th April 2015) - Tian, Zhen; Wu, Kan; Kong, Lingchen; Yang, Nan; Wang, Yao; Chen, Rong; Hu, Weisheng; Xu, Jianqiu; Tang, Yulong
Abstract: Liquid-phase exfoliated 2D material multilayer MoS2 is transferred onto a gold mirror and its saturable absorption at the 2  µ m wavelength region is experimentally observed. This transferred MoS2 saturable absorber has a modulation depth of 13.6% and a saturation intensity of 23.1 MW cm −2 . This saturable absorber is integrated into a linear Tm 3+ fiber laser cavity, and stable fundamental-frequency mode-locking operation is realized at 2  µ m with pulse energy of 15.5 nJ, pulse width of ~843 ps, and a repetition rate of 9.67 MHz. The laser spectral width is ~17.3 nm with a center wavelength of 1905 nm. This first presence of mode-locking with multilayer MoS2 sheets in the 2  µ m wavelength region verifies that multilayer MoS2 is a good candidate for broadband mode-locking comparable to graphene, as well as a good mode-locker for achieving high pulse energy.